The relative peak power output of amateur mountain bikers is inversely correlated with body fat but not with fat-free mass - Rhaí André Arriel; Juliana Alves Graudo; Jorge Luiz Duarte de Oliveira; Guilherme Guedes Silva Ribeiro; Anderson Meireles; Moacir Marocolo (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aims: To evaluate whether body mass (BM) and body composition may influence mountain bike cycling performance. Methods: Forty male amateur mountain bikers attended the laboratory on two non-consecutive days. At the first visit, anthropometric measures (height, BM, body fat [BF], fat-free mass [FFM] and body mass index [BMI]) and familiarization to incremental cycling test were performed. On the second visit, cyclists performed again the incremental cycling test to measure peak power output (PPO), peak power output relative to BM (PPO-BM), and time to exhaustion (TE), which were posteriorly correlated with BM and anthropometric measures. Results: A low and moderate significant correlation were observed between TE and BM (p<0.01; r=0.40) and FFM (p<0.01; r=0.56). Moderate significant correlation was found between PPO and BM (p<0.01; r=0.45), BMI (p=0.03; r=0.35) and strong with FFM (p<0.01; r=0.59). Also, PPO-BM significantly correlated with BM (p=0.04; r=-0.31), BMI (p=0.02; r=-0.35) and BF (p<0.01; r=-0.55). No other significant correlations were observed. Conclusion: Considering PPO-BM as mainly performance variable, BM and BF can be a determining factor in mountain biking performance but FFM did not.